Evaluating the Impact of Hepatic or Renal Impairment on Tanimilast (CHF6001) Pharmacokinetics: Two Open‐Label, Parallel‐Group, Single‐Center Studies - Annalisa Piccinno; Maria Gloria Pittelli; Deborah Balzano; Elisa Rizzo; Pooja Bellatti; Chiara Rostello; Aida Emirova (Clinical and Translational Science)
ABSTRACT Tanimilast is an inhaled phosphodiesterase‐4 inhibitor in development for chronic obstructive pulmonary disease and asthma. We conducted two studies to evaluate tanimilast pharmacokinetics, one in subjects with mild, moderate, or severe hepatic impairment and matched healthy controls, and one in subjects with mild, moderate, or severe renal impairment and matched healthy controls. Both studies were single‐center, open‐label, and parallel group; all subjects inhaled a single 800 μg dose of tanimilast. The primary objective was to evaluate systemic exposure of tanimilast in subjects with hepatic or renal impairment, and in matched healthy subjects, in terms of maximum observed plasma concentration (Cmax) and area under the plasma concentration–time curve from time 0 to the last quantifiable concentration (AUC0–t). A total of 44 subjects were enrolled in each study (8 with mild, moderate or severe hepatic/renal impairment, and 20 controls), all of whom completed. In the hepatic impairment study, there were no statistically significant differences in tanimilast Cmax and AUC0–t between controls and subjects with mild or moderate impairment. For severe hepatic impairment, Cmax did not differ significantly from controls, but AUC0–t increased by 104% (point estimate of ratio [90% confidence interval], 204.03 [134.36; 309.81]). In the renal impairment study, there were no statistically significant differences in tanimilast Cmax and AUC0–t between controls and subjects with mild‐to‐severe impairment. Three subjects had adverse events in each study, all mild‐to‐moderate, and none were study treatment related. These data suggest that the pharmacokinetics of tanimilast are not impacted by mild‐to‐moderate hepatic impairment, or by mild‐to‐severe renal impairment. Trial Registration: ClinicalTrials.gov (hepatic impairment NCT05373953; renal impairment NCT05431426) and EudraCT (hepatic impairment 2021‐003729‐31; renal impairment 2021‐005567‐43)